DESIGN SYSTEM INFORMATION CASHIER WEBSITE BASED SPIRAL METHOD SHOP VINNY KITCHEN MDO - Andreas Sugiharto; Ai Rosita (JURNAL DARMA AGUNG, 2023)
Cashier system in shop business entities Vinny Kitchen Mdo is still using Sales services are still done manually, namely cashiers only use calculations manual with a calculator and data collection of goods is still manual and resulted very ineffective and efficient in doing transaction. Facility And service to cashier expected can given in a manner automatic so that No bother in transactions with customers, and if there is a cashier does not need to provide the same service in a manner manuals. Model implementation system cashier based web possible system used by cashiers and admins to automatically calculate orders for goods in transaction sale. Use system cashier based web This can see chart sales that are entered in the system so that store owners can monitor increases or a decrease in transactions. The method to be used is the Spiral Method that is, a software process model that incorporates the iterative form of the model prototyping aspect control And systematics. Design system information cashier sale product shop vinny kitchen mdo in do transaction, processing data, And Web-based automatic printing of reports when running will occur change system Which before manual be computerized.